2003
DOI: 10.1667/0033-7587(2003)159[0651:hmmato]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Minisatellite Mutations among the Offspring of Estonian Chernobyl Cleanup Workers

Abstract: A single accidental event such as the fallout released from the Chernobyl reactor in 1986 can expose millions of people to non-natural environmental radiation. Ionizing radiation increases the frequency of germline mutations in experimental studies, but the genetic effects of radiation in humans remain largely undefined. To evaluate the hereditary effects of low radiation doses, we compared the minisatellite mutation rates of 155 children born to Estonian Chernobyl cleanup workers after the accident with those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
3
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 22 publications
2
35
3
1
Order By: Relevance
“…In addition, a number of studies have failed to detect an increase in mutations among the children of Chernobyl cleanup workers (34)(35)(36)(37). This may be caused largely by the lack of useful tools and approaches to evaluate the potential for agents to produce heritable effects.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a number of studies have failed to detect an increase in mutations among the children of Chernobyl cleanup workers (34)(35)(36)(37). This may be caused largely by the lack of useful tools and approaches to evaluate the potential for agents to produce heritable effects.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these observations, a radiosensitive window was proposed in which certain stages of the spermatogenesis are sensitive to low-dose and low dose-rate radiations for the induction of minisatellite mutation. Another study on the children of Estonian clean-up workers suggested a slight but nonsignificant elevation of the mutation frequency only when the dose to the fathers was above 0.2 Sv (Kiuru et al, 2003).…”
Section: Radiation Induction Of Minisatellite Instability In Humans: mentioning
confidence: 96%
“…Although extensively researched in humans (Jeffreys et al, 1985bJeffreys, 1987), DNA fingerprint analysis has shown that they are omnipresent throughout the genome of most organisms and higher eukaryotes (Burke & Bruford, 1987;Jeffreys et al, 1987;Gilbert et al, 1990;Andersen & Nilsson-Tillgren, 1997;Bois et al, 1998a). Shown to exhibit high levels of germline mutation rates (up to 15% per gamete) (Vergnaud et al, 1991), minisatellites have thus been successfully utilised as a tool for monitoring DNA mutation following exposure to environmental doses of mutagenic agents in both human (Dubrova et al, 1996(Dubrova et al, , 1997Kodaira et al, 1995Kodaira et al, , 2004Satoh et al, 1996;Livshits et al, 2001;Kiuru et al, 2003), and animal populations (Yauk & Quinn, 1996;Yauk et al, 2000).…”
Section: Minisatellitesmentioning
confidence: 99%